Tartil and Tajweed Training for Juz 'Amma for Class 6A Students of SDN Sukun 3, Malang City - Mar'atul Fitriayu Azizah; Muhammad Husni (Universitas PGRI Sumatera Barat, 2026)
This Student Creativity Program – Community Service (PKM-KM) aims to improve the ability to read the Qur'an with tartil and to introduce the basics of recitation to Grade 6A students at SDN Sukun 3 Malang City. The background of this activity stems from the low proficiency of students in reading the Qur'an correctly in accordance with tajwid rules. This issue is caused by limited practice intensity, a lack of diverse teaching methods, and insufficient time allocation in Islamic Religious Education classes. The activity was conducted over three days using an educational and participatory approach, which included theoretical delivery of material, Qur'anic reading practice using the talaqqi and simaan methods, and evaluation through pre-tests and post-tests. This program not only enhances students' cognitive and technical skills but also fosters their love for the Qur'an and helps them develop a regular reading habit. Furthermore, the activity received positive support from teachers and the school as part of their efforts to strengthen character-based religious education. It is hoped that this program can be replicated in other elementary schools as a tangible contribution to nurturing a Qur'anic generation from an early age.